2018
DOI: 10.1111/tpj.13795
|View full text |Cite
|
Sign up to set email alerts
|

The role of water in plant–microbe interactions

Abstract: SUMMARYThroughout their life plants are associated with various microorganisms, including commensal, symbiotic and pathogenic microorganisms. Pathogens are genetically adapted to aggressively colonize and proliferate in host plants to cause disease. However, disease outbreaks occur only under permissive environmental conditions. The interplay between host, pathogen and environment is famously known as the 'disease triangle'. Among the environmental factors, rainfall events, which often create a period of high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
100
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(111 citation statements)
references
References 83 publications
(110 reference statements)
1
100
0
10
Order By: Relevance
“…Generally, the interplay between host, pathogen and environment is famously known as the ‘disease triangle’ (Stevens, ). Among environmental factors, periods of high atmospheric humidity have repeatedly been shown to promote disease outbreaks in plants, suggesting that the availability of water is crucial for pathogenesis (Xin et al ., ; Aung et al ., ). A variety of pathogenic Pseudomonas strains create an aqueous habitat in the leaf apoplast during the early infection period.…”
Section: Discussionmentioning
confidence: 97%
“…Generally, the interplay between host, pathogen and environment is famously known as the ‘disease triangle’ (Stevens, ). Among environmental factors, periods of high atmospheric humidity have repeatedly been shown to promote disease outbreaks in plants, suggesting that the availability of water is crucial for pathogenesis (Xin et al ., ; Aung et al ., ). A variety of pathogenic Pseudomonas strains create an aqueous habitat in the leaf apoplast during the early infection period.…”
Section: Discussionmentioning
confidence: 97%
“…Some epiphytes may be injected into the internal space of the leaf and colonize as endophytes. The distribution pattern of the phyllosphere microorganisms is not even, mostly bacteria colonize at the epidermal wall junctions, specifically in the grooves and the veins or stomata or at the base of trichomes (Melotto et al 2008), also found in the cuticle layer, near hydathodes and stomatal pits (Aung et al 2018). The microbial load is higher at the lower leaf surface perhaps the lower leaf surface contains thin cuticle, stomata, and/or trichomes (Beattie and Lindow 1999).…”
Section: Microbial Diversity In the Phyllospherementioning
confidence: 98%
“…Aung et al . () describe the effect of water on the different facets of the infectious process: rhizosphere and phyllosphere microbes, stomatal functioning, defense mechanisms, and drought tolerance. Indeed, simultaneous exposure to biotic and abiotic stresses is likely the rule in plant‐microbe interactions: in the last article, Bai et al .…”
mentioning
confidence: 99%
“…Among the environmental factors that influence disease development, high atmospheric humidity has been often found to influence plant-pathogen interactions. Aung et al (2018) describe the effect of water on the different facets of the infectious process: rhizosphere and phyllosphere microbes, stomatal functioning, defense mechanisms, and drought tolerance. Indeed, simultaneous exposure to biotic and abiotic stresses is likely the rule in plant-microbe interactions: in the last article, Bai et al (2018) examine the complexity of plant responses to combined salinity and pathogen stresses and highlight the role of the ABA signaling pathway, among other possible pathways mobilised in response to abiotic stress.…”
mentioning
confidence: 99%